Maumu apa, Malaysia? konflik Indo-Malay dari kacamata seorang WNI di Malaysia - Lazuardi, Genuk Ch (Gramedia Pustaka Utama, 2009)
Author's account as Indonesian citizen on sociocultural problems between Indonesia and Malaysia.